Estudo da expressão gênica e proteica de PD-1, PD-L1 E CTLA-4 em pacientes com neoplasia mielodisplásica - Garcia, Yhasmine Delles Oliveira (2023)
The pathogenesis of Myelodysplastic Syndromes (MDS) is characterized by intense immune dysregulation and evasion of the immune system, mediated by the programmed death 1 PD-1, programmed death-ligand 1 PD-L1, and cytotoxic T-lymphocyte-associated antigen 4 CTLA-4 checkpoint receptors. The blockade of these receptors has been utilized as a therapeutic target in MDS. The aim of this study was to evaluate the protein and gene expression of PD-1, PD-L1, and CTLA-4, and associate them with sociodemographic, clinical, and prognostic profiles in patients with MDS. This was a cross-sectional, analytical, and descriptive study involving 34 patients with MDS undergoing treatment at the HUWC and 15 healthy individuals (control group). Sociodemographic, clinical, and laboratory data were obtained from medical records. The expression of PD-1, PD-L1, and CTLA-4 proteins was evaluated by Immunohistochemistry (IHC), and gene expression was assessed by RT-PCR. Statistical analyses were performed using SPSS 20.0 and GraphPad Prism 6.0, with significance set at p<0.05. The mean age was 69.91±16.33 years, with 52.94% females and 52.94% from the countryside of the state of Ceará, Brazil. MDS with low blast counts constituted 20.29% of the patients, and 44.2% had a low-risk IPSS-R score. Protein expression was positive in 52.18%, 78.26%, and 86.95% for PD-1, PD-L1, and CTLA-4, respectively, in Bone Marrow (BM) biopsies of MDS patients, and there was a significant difference between CTLA-4 and PD-1 (p=0.034). PD-L1 showed higher intensity compared to PD-1 (p=0.039). Positive staining for PD-L1 was also observed in 47.82% of megakaryocytes in MDS patients. In multivariate analysis, protein expressions were associated: PD-1 with female sex (p=0.039) and myelofibrosis (p=0.038), and CTLA-4 with neutrophil count (p=0.015) and dysgranulopoiesis (p=0.015). Positive gene expression of PD-1, PD-L1, and CTLA-4 was observed in 28.57%, 23.81%, and 33.33% of MDS patients, respectively, with no difference compared to the control group. In multivariate analysis, PD-1 gene expression was associated with age ≤ 70 years (p=0.006); PD-L1 with transfusion dependence (p=0.029) and hypoplastic subtype (p=0.044). A lower Overall Survival (OS) rate was observed in MDS patients with isolated positive expression of PD-L1 and when it was associated with CTLA-4. Reduced OS was related to age >70 years, normal platelet count, hypercellular marrow, dysmegakaryopoiesis, and progression to Acute Myeloid Leukemia (AML). Regarding Progression-Free Survival (PFS), variables age >70 years, hypercellular marrow, and dysmegakaryopoiesis were associated with shorter PFS, while positive expression of PD-L1+CTLA-4+ was predictive of lower PFS (CI 1.96-90.61; p=0.013). In conclusion, at the diagnosis of MDS, positive gene and protein expression of PD-1, PD-L1, and CTLA-4 are increased and are associated with a worse prognosis, emphasizing their relevance as predictive prognostic biomarkers and in determining eligibility for personalized treatment in MDS patients.